SOLARIS project: a portable 3D-printed bioaerosol sampler for environmental bacterial collection - Pedro Henrique Dobroes Fonseca; Filipe Miguel Borgas Henriques Duarte; Frederico Silva de Sousa Alves; Jose Alberto de Jesus Borges; Susana Isabel Pinheiro Cardoso; Vania Cristina Henriques Silverio; Wilson David Talhao Antunes (Royal Society Open Science)
Bioaerosols, a subset of aerosols released from the biosphere, can carry pathogens, and include particles with diameters from nanometres to a few micrometres. They can remain suspended indoors and travel significant distances. Bioaerosol studies play a vital role in public health, as bioaerosols are an effective route for human and animal pathogen transmission, especially in animal production and handling facilities, which are considered hotspots for the emergence of zoonotic pathogens. The ‘One Health‘ approach, which interconnects human, animal and environmental health, underscores the need for robust biomonitoring and biosurveillance systems. We introduce the SOLARIS project, a novel bioaerosol sampler manufactured through three-dimensional printing with a biocompatible material. Our sampler is compact, portable and uses a liquid collection medium, increasing bioefficiency. Our sampler’s laboratory testing demonstrated the successful separation of viable Escherichia coli bacteria from artificially generated bioaerosols. Collected samples were found suitable for downstream analysis methods such as culturing, mass spectrometry, molecular detection and electron microscopy. A field trial at a swine facility was performed, in which Clostridioides difficile spores were successfully collected from bioaerosols and identified using microbiological and molecular methods, reinforcing our sampler’s utility and emphasizing the significance of incorporating aerosol samples in research studies within the One Health approach.